1992
DOI: 10.1103/physrevlett.68.2204
|View full text |Cite
|
Sign up to set email alerts
|

Definitive identification ofDcenters in GaAs quantum wells by tilt-induced line splitting in a magnetic field

Abstract: D ~ centers have been unambiguously identified in GaAs/(Ga,Al)As quantum wells by analysis of the dependence of the observed photoconductivity spectrum on the applied magnetic field and sample orientation. Theoretical investigations show that in magnetic fields of interest the D ~ transitions do not involve photoionization of the centers as has been previously supposed but proceed from the ground state to discrete p-\-or p + i-like D~ levels, which lie above the N-0 and 7V = 1 Landau-level energies, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 11 publications
(16 reference statements)
1
29
0
Order By: Relevance
“…Other results obtained in [7] correspond to the intermediate and narrow QWs (d/a 0 ≤ 2) for which the energies W are positive. A discrepancy in the binding energy is of the same order as those obtained by the various numerical methods [2,3,6,7]. It is therefore concluded that the method developed can be readily extended to the problem of the charged donor in the presence of electric and strong magnetic fields.…”
Section: Equation (12) Then Becomesmentioning
confidence: 55%
See 1 more Smart Citation
“…Other results obtained in [7] correspond to the intermediate and narrow QWs (d/a 0 ≤ 2) for which the energies W are positive. A discrepancy in the binding energy is of the same order as those obtained by the various numerical methods [2,3,6,7]. It is therefore concluded that the method developed can be readily extended to the problem of the charged donor in the presence of electric and strong magnetic fields.…”
Section: Equation (12) Then Becomesmentioning
confidence: 55%
“…Using the Monte Carlo method, Pang and Louie [2] calculated the binding energy of the ground state of the D − positioned at the centre of the narrow QW. Mueller et al [3] and Dunn et al [4] studied the problem by the variational approach based on the Chandrasekhar-type [5] and Gaussian-like trial functions, respectively. Dzubenko and Sivachenko [6] formed the wavefunction of the D − from the wavefunctions of the free electron corresponding to several Landau levels and the ground size-quantization level.…”
Section: Introductionmentioning
confidence: 99%
“…The confinement effect imposed by the quantum well on both the D --and D 0 binding energies in different semiconductor heterostructures has been analyzed in a considerable number of theoretical investigations [11][12][13][14][15][16][17][18][19][20][21]. The diffusion quantum Monte Carlo [11,12] and variational [13][14][15][16][17][18][19][20][21] methods have been used to calculate the D --groundstate binding energy in quantum wells (QWs) and quantum dots (QDs).…”
Section: Introductionmentioning
confidence: 99%
“…Shallow-negative donors D ± ± (i.e. neutral shallow donors that bind an additional electron) have been experimentally observed [1,2] in GaAs±(Ga,Al)As quantum wells (QWs). It has been also demonstrated [3,4] by variational calculations that the two-dimensional D ± ± binding energy is about ten times larger than the three-dimensional one, and the impurity mean-value radius is reduced by half when its form is changed from spherical to planar.…”
mentioning
confidence: 99%